2009
DOI: 10.1158/1541-7786.mcr-08-0117
|View full text |Cite
|
Sign up to set email alerts
|

The Fer Tyrosine Kinase Cooperates with Interleukin-6 to Activate Signal Transducer and Activator of Transcription 3 and Promote Human Prostate Cancer Cell Growth

Abstract: Androgen withdrawal is the most effective form of systemic therapy for men with advanced prostate cancer. Unfortunately, androgen-independent progression is inevitable, and the development of hormone-refractory disease and death occurs within 2 to 3 years in most men. The understanding of molecular mechanisms promoting the growth of androgenindependent prostate cancer cells is essential for the rational design of agents to treat advanced disease. We previously reported that Fer tyrosine kinase level correlates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 48 publications
0
39
2
Order By: Relevance
“…Up-regulation and activation of FER has been reported in multiple cancers, including lung (Rikova et al 2007), hepatic ), prostate (Zoubeidi et al 2009), breast (Albeck and Brugge 2011), and ovarian cancer (Ren et al 2012). Its oncogenic role has been implicated in the control of cell motility and invasion, suppression of apoptosis, and drug resistance (Greer 2002;Craig 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Up-regulation and activation of FER has been reported in multiple cancers, including lung (Rikova et al 2007), hepatic ), prostate (Zoubeidi et al 2009), breast (Albeck and Brugge 2011), and ovarian cancer (Ren et al 2012). Its oncogenic role has been implicated in the control of cell motility and invasion, suppression of apoptosis, and drug resistance (Greer 2002;Craig 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Because VE-cadherin internalization is induced by its serine/threonine or tyrosine phosphorylation (10,20), and ligation of IL-6 with its receptor gp130 has been shown to activate PI3-kinase and Src kinase family member, Fer (40,42), it is possible that IL-6-induced VE-cadherin dissociation from adherens junctions may be mediated by gp130-Fer/PI3- kinase mechanism, although analysis of this mechanism was not the focus of this study. Both the IL-6-induced EC permeability and Stat3, NF-B, and p38 signaling was abolished by Jak inhibition suggesting that potential IL-6-induced activation of Src is downstream of Jak kinase.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have identified Fer activation or upregulation in a number of different cancers, including lung (14), hepatic (15), prostate (16), and triple-negative breast cancer (17). Overexpression of Fer was also linked to quinacrine resistance and enhanced activation of NFkB pathway (5).…”
Section: Introductionmentioning
confidence: 99%